Creative Proactive-Concluding Theory of Motivating - Blašková, Martina (Business: Theory and Practice, 2010)
he article deals with necessity to change the understanding of human resource philosophy to the new philosophy: philosophy of human potential. In these intentions, it is very important to motivate human potential in the organisations. But, in the area of motivating, situation within the organisations isn’t sufficient. Thereto the article gives an introductive presentation of a new theory of motivating: creative proactive-concluding theory of motivating. The theory leads the managers to utilize an individual approach to their employees and use perceptiveness to the needs and expectations of the employees and organisational environment. The model of theory contains a demand to harmonize existing motivational programs with new original motivational elements. It is based upon the trust between the manager and employee. The model also reflects the need to create differenced motivational programs for each employee and manager.